1994
DOI: 10.1002/mpo.2950220609
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric hodgkin's disease in costa rica: Twelve years' experience of primary treatment by chemotherapy alone, without staging laparotomy

Abstract: This is a prospective and nonrandomized study in which 86 children with previously untreated Hodgkin's disease (HD) were clinically staged (CS) and treated with chemotherapy (CT) alone. Fifty-two (CS IA-38, IIA-7, IIB-3, IIIA-4) received six courses of cyclophosphamide, vinblastine, procarbazine, and prednisone (CVPP). Ten (CS IA with peripheral nodes) received only three courses of CVPP with a reinforcement of C on day 8. Twenty-four (CS IIIB-18, IVA-2, IVB-4) received six courses of CVPP alternating with six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
1
13
1
1
Order By: Relevance
“…However, when a relapse occurs, the outcome, as based on our two observations, is poor. The decrease in DFS in patients with more advanced stage HD treated without radiotherapy as reported by Lobo-Sanahuja et al [16] using CVPP (cyclophosphamide, vinblastine, procarbazine, prednisone)/ EBO (epirubicin, bleomycin, and vincristine) has not been seen in our patients, but as only one of our patients was CS IV, we cannot make a conclusion for this category of patients. In our study to date only one child with initially CS I and another child with CS II have relapsed.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…However, when a relapse occurs, the outcome, as based on our two observations, is poor. The decrease in DFS in patients with more advanced stage HD treated without radiotherapy as reported by Lobo-Sanahuja et al [16] using CVPP (cyclophosphamide, vinblastine, procarbazine, prednisone)/ EBO (epirubicin, bleomycin, and vincristine) has not been seen in our patients, but as only one of our patients was CS IV, we cannot make a conclusion for this category of patients. In our study to date only one child with initially CS I and another child with CS II have relapsed.…”
Section: Discussioncontrasting
confidence: 44%
“…Sackman-Muriel et al [23] concluded from a randomized study that comparable results can be achieved using chemotherapy with or without radiotherapy. Recently, Lobo-Sanahuja et al [16] reported on 86 children with DFS rates of 90% and 60% for CS I-IIIA and CS IIIB-IV, treated with chemotherapy only. In most studies, however, only a few CS IV patients have been included.…”
Section: Discussionmentioning
confidence: 99%
“…In this stage, systemic symptoms are noted in some 65-80% of patients [21,26,28,30]. Among 783 of our patients with HD, stage IV was diagnosed in 57 children (7.3%).…”
Section: Discussionmentioning
confidence: 89%
“…In our material (Table I), in the years 1971-1982, hepatic involvement was predominant (41-43%), followed by lung involvement (50%), but differences were not significant. Reports from Costa Rica [26], Turkey [29], and Italy [21] describe lymphocyte depletion type in patients with stage IV HD occurring in 66.7%, 26%, and 10%, respectively. On the other hand, pediatric population data compiled in the United States show no lymphocyte depletion type in any HD stage [30].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation